KEPATUHAN PENGGUNAAN HELM SAAT BERKENDARA DALAM MENCEGAH CEDERA KEPALA PADA PENGENDARA REMAJA - Nobrihas, Reni Y. T.; Mahoklory, Serly S.; Mbanga, Erdianus; Sellan, Rudolf N. (Lasalle Health Journal, 2023)
Introduction: The large number of adolescents riding motorcycles coupled with the increasing number of accidents in the world has caused the number of disabilities and even deaths to increase. Head injuries are one of the fatal consequences that often occur due to accidents. Compliance with helmet use was very important when driving because it can reduce the risk of danger due to accidents. Objective: This study aims to determine the factors associated with compliance with helmet use when riding in preventing head injuries in adolescent drivers. Method: The research method used was correlation analysis with cross sectional approach. In a cross-sectional study, the time of measurement and observation of data was carried out once at a time, which was carried out on the independent variables and dependent variable. The sampling technique uses total sampling. Results: Data were analized using Spearman Rank which shows that the ρ-value of the family factors = 0,000 < 0,05, the ρ-value of the economic factors = 0,000 < 0,05, the ρ-value of the individual factors = 0,000 < 0,05, the ρ-value of the socio-cultural factors = 0,000 < 0,05. Conclusion: It can be concluded that there was a relationship between family factors, economic factors, individual factors, and socio-cultural factors with complience with helmet use when riding in preventing head injuries in adolescent drivers.